2021
DOI: 10.21203/rs.3.rs-479157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Ensemble Intrusion Detection Model For Internet of Things Network

Abstract: The advancements of technology are playing a significant role in protecting the data from intruders. In this paper, a robust network intrusion detection system (IDS) is proposed for Internet of Things (IoT) using deep learning approaches. The type of intrusions we adopted in this work are distributed denial of service (DDoS) and replay attack. Our proposed work is divided into three sections, namely, node deployment, threat detection modelling, and prevention modelling. For detection, ensemble algorithm has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Choudhary et al [ 33 ] propose an IDS based on deep learning using SVM and DNN. Since SVMs are binary classifiers, only two routes were classified at a time for the appropriate route to be shown.…”
Section: Existing Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Choudhary et al [ 33 ] propose an IDS based on deep learning using SVM and DNN. Since SVMs are binary classifiers, only two routes were classified at a time for the appropriate route to be shown.…”
Section: Existing Workmentioning
confidence: 99%
“…Based on the studies reviewed in the previous sections, we found the following: Most papers targeted the IoT network environment when designing their systems (e.g., [ 6 , 8 , 13 , 18 , 22 , 23 , 28 , 33 ]). Few papers targeted other environments, such as wireless medical sensor networks (e.g., [ 20 ]).…”
Section: Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the paper discussed the result that was defined by using the CCNx 1.0 protocol. Sarika et al [45] presented a network intrusion detection system (IDS) to be applied to the IoT. This paper focused on some attacks such as DoS and DDoS attacks using ML algorithms to detect all possible intrusions, such as deep neural network (DNN) and SVM.…”
Section: Related Work On Icn-based Iot With Machine Learning Technolo...mentioning
confidence: 99%
“…A multi-agent model was proposed using deep learning in [16]. Many researchers have extensively studied the vulnerabilities of RPL, including various internal attacks, for instance, Sybil, rank, sinkhole, version number, blackhole, neighbor, DIS, DAO, and selective-forwarding attacks [14,[17][18][19]. (DIS and DAO are explained in Section 3.1.2).…”
Section: Related Workmentioning
confidence: 99%